A North American Cohort of Anti‐SAE Dermatomyositis: Clinical Phenotype, Testing, and Review of Cases. Issue 5 (28th March 2021) - Albayda, Jemima; Mecoli, Christopher; Casciola‐Rosen, Livia; Danoff, Sonye K.; Lin, Cheng Ting; Hines, David; Gutierrez‐Alamillo, Laura; Paik, Julie J.; Tiniakou, Eleni; Mammen, Andrew L.; Christopher‐Stine, Lisa
Abstract : Objective: Antibodies against the small ubiquitin‐like modifier (SUMO) activating enzyme (SAE) are one of the rarer specificities associated with dermatomyositis (DM). The purpose of this study is to describe the clinical characteristics of patients with anti‐SAE autoantibodies in a North American cohort and to ascertain cancer prevalence. We also describe the performance characteristics of the line blotting (Euroimmun) method for antibody detection compared with an immunoprecipitation‐based assay. Methods: Sera from 2127 patients suspected of having myositis were assayed for myositis‐specific autoantibodies using the Euroimmun platform. Those positive for SAE autoantibodies were assayed by a second method (immunoprecipitation) for confirmation. Only those cases positive by both methods were taken as definite cases of anti‐SAE–positive DM. Chart reviews of these patients were completed to obtain information on clinical characteristics, cancer history, and treatment. Results: Forty‐three of 2127 sera were anti‐SAE autoantibody positive by Euroimmun (≥15 units, +); of these, only 19 were confirmed positive by immunoprecipitation. All 19 cases had skin involvement and varying presentations of muscle, lung, and joint disease. Cancer occurred coincident with DM in two patients, and cancers were detected more than 5 years from symptom onset in three patients. In a population of suspected inflammatory myositis, a higher cutoff on line blot testing (≥36 units, ++) yielded better agreement with immunoprecipitation methods. Conclusion: SAE autoantibodies associate with a clinical phenotype of DM, which most commonly presents with a rash first, followed by muscle involvement and varying extramuscular involvement. As coincident cancer was seen in anti‐SAE–positive DM, judicious malignancy screening may be warranted.